Pemalsuan Akta Autentik Sebagai Aspek Pidana Notaris - M. Jamil (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2019)
The notary is known as a respected official in accordance with the mandate of the law. In Article 1 paragraph 1 of the Amended UUJN, it is stated that a Notary Public is authorized to make an authentic deed and has other authorities as referred to in this Law or based on other laws. Sometimes the labeling of the word